The impact of levothyroxine therapy on pregnancy and neonatal outcomes in euthyroid pregnant women with thyroid autoimmunity: A systematic review, meta-analysis and trial sequential analysis - Chen, Jingjing; Jiao, Xue-Feng; Zhang, Li; Zhang, Miao; Zeng, Linan; Liu, Dan; Li, Hailong; Zou, Kun; Wei, Qiang; Zhang, Lingli (Frontiers in Pharmacology, 2023)
Background: At present, only one systematic review has explored the effect of levothyroxine (LT4) in euthyroid pregnant women with thyroid autoimmunity. However, this study suffers from a series of problems [such as merging different types of research for meta-analysis, lacking neonatal outcomes, and so on], and cannot provide satisfactory results. So, this systematic review, meta-analysis and trial sequential analysis (TSA) was performed to assess the effect of LT4 in euthyroid pregnant women with thyroid autoimmunity, with the aims of providing more comprehensive evidence for clinical practice. Methods: Medline (Ovid), Embase (Ovid), and Cochrane Central Register of Controlled Trials were electronically searched from database inception to March 2022. RCTs and cohort studies that reported the impact of LT4 therapy on pregnancy and neonatal outcomes in euthyroid pregnant women with thyroid autoimmunity were included. Meta-analyses of RCTs and cohort studies were performed separately, and further meta-analyses were performed by only including studies with low and moderate risk of bias. We used the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach to evaluate the quality of evidence, and performed TSA to test whether the evidence was sufficient. Results: A total of six RCTs and five cohort studies comprising 2901 euthyroid pregnant women with thyroid autoimmunity were included. There were no statistically significant differences between LT4 group and control group in all outcomes, including miscarriage [RR=0.85, 95%CI (0.69,1.05), P= 0.14, I2=1%], preterm birth [RR=0.80, 95%CI (0.59,1.08), P=0.14, I2=0%], preeclampsia [RR=0.68, 95%CI (0.12, 3.91), P=0.66, I2=0%], placenta abruption [Peto’ OR=0.14, 95%CI (0.00, 6.94), P=0.32, I2=0%], birth weight [MD=-36.00, 95%CI (-170.41, 98.41), P=0.60, I2=0%], gestational age at delivery [MD=-0.10, 95%CI (-0.61, 0.41), P=0.70, I2=0%] and neonatal admission [RR=1.33, 95%CI (0.21, 8.58), P=0.76, I2=0%]. TSA showed that the results for all outcomes were insufficient and inconclusive. The GRADE assessments showed that the evidence for 4 outcomes (miscarriage, preterm birth, birth weight and gestational age at delivery) were rated as moderate quality, and the other outcomes were rated as low or very low quality. Conclusions: Our study found no evidence of benefit of levothyroxine therapy on pregnancy and neonatal outcomes in euthyroid pregnant women with thyroid autoimmunity.